Analysis of the Factors leading to Severe Acute Maternal Morbidity and Maternal Mortality during COVID 19 Pandemic - Shrestha, Junu; Thapa, Sudiksha; Sharma, Nidhish (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: To determine prevalence, causes and factors leading to severe acute maternal morbidity and mortality during COVID 19 pandemic. Methods: The was a cross sectional observational study conducted in the department of Obstetrics and Gynaecology of Manipal teaching hospital from March 2020 to February 2022 amid COVID 19 pandemic. Women who sustained severe acute maternal morbidity (according to World health organization organ system criteria) and maternal deaths during pregnancy, labour and six weeks postpartum were included. Maternal characteristics, total live births, pregnancy outcome, causes and factors leading to morbidity and mortality were noted. The acquisitioned data was analyzed using Statistical Package for Social Sciences version 21. Results: There were 37 cases of severe acute maternal morbidity and 2 cases of maternal deaths. The severe acute maternal morbidity ratio was 9.4 per 1000 live births and maternal mortality ratio was 51 per 100,000 live births. Therefore, severe acute maternal morbidity mortality ratio was 18.5:1 and mortality index 5.1%. Haematological and coagulation system (45.9%) and neurological system (29.7%) were the common organ systems involved. Hypertensive disorders (40.5%) and haemorrhage (32.4%) were the main causes of severe acute morbidity. Both maternal deaths occurred due to eclampsia. There was no severe acute maternal morbidity or mortality due to COVID infection in pregnancy. Delay in seeking and reaching to the health centre (65%) was major delay leading to severe morbidity and mortality. Conclusions: Indices and causes of severe acute maternal morbidity and mortality during COVID 19 pandemic was not worse compared to those prior to COVID 19 pandemic. Primary delay in seeking and reaching health care was the main factor leading to severe morbidity and mortality.